The influence of ppary ligands on the expression of FOXP3 in natural t-regulatory cells in balb/c and type 1 diabetes mouse model - Zulkafli, Nor Effa Syazuli (2015)
Natural CD4+CD25+Foxp3+ T regulatory cell (nTreg) is a subset of regulatory T cell that is derived from the thymus. The immunodownregulatory function of nTreg cells is critical in mediating peripheral self-tolerance. Concordantly, the antiinflammatory properties of peroxisome proliferator-activated receptor (PPAR have been intensely studied in recent years. Given their crucial role in immune regulation, the current study was conducted to decipher the modulatory mechanism by PPAR ligands in nTreg cells of BALB/c, and the Type 1 Diabetic (T1D) model, Non Obese Diabetic (NOD) as well as in the Non Obese Resistant (NOR) mice. Initially, we optimized the time-points and the concentrations of IL-2 for in vitro culture of nTreg cells in BALB/c mice. Subsequently, the functional analysis of isolated nTreg cells of BALB/c mice was measured.